Maxillary Sinus Squamous Cell Carcinoma Presenting with Fatal Tumor Lysis Syndrome: A Case Report and Review of the Literature - Mirna Abboud; Ali Shamseddine (Case Reports in Oncology, 2009)
Acute tumor lysis syndrome (TLS) is a condition resulting from rapid destruction of tumor cells and subsequent massive release of cellular breakdown products. It has been described following the treatment of many hematologic and solid malignancies. However, spontaneous TLS has rarely been described. Here we report a case of spontaneous TLS that occurred in a patient with a treated maxillary squamous cell carcinoma (SCC) presenting with diffuse liver metastases, which is an infrequent site of distant metastases.